THE WISDOM AND EDUCATIONAL VALUES OF THE VERSES OF MUHKAMAT AND MUTASYABIHAT IN THE QUR’AN - Achmad Sopian (International Conference on Social and Islamic Studies, 2021)
This study aims to analyze the wisdom and educational values of the verses ofMuhkamat and Mutasyabihat in the Qur'an. Al-Quran is a guide, a resource andreference for all people. All things related to Al-Quran is deemed noble andcommendable. Therefore, the study of Al-Quran still continues because it containsvery broad and deep, including problems muhkam and mutasyabih. “Ayat muhkam”is the subject of the Qur'an, and there are some ”ayat mutasyabih” whose meaningis restored to “ayat muhkamat”. Takwil to “ayat mutashabihat” done not only bykhalaf generation, but the generation of the Salaf (the first three centuries of Hijra)also did the same thing. The method used in this research is library research wherethe writer tries to find, compile and analyze various information through variousrelated sources. The Qur'an has functions as a bayan (explanatory) and hudan(guidance) which contains an explicit verse or muhkam. Besides, it also hasfunctions as the greatest miracle and literary book in human history which containsan implicit verse or mutasyabih that will never end to be studied and researched.Muhkamat and mutasyabihat verses are two complementary things in the Qur'an.There is an immeasurable wisdom and educational value for both. Therefore, inlearning and understanding both is as well as learning the wisdom of decreasing theQur'an itself.